The passive haemagglutination reaction with sonicated T. pallidum (Nichols strain) in the serodiagnosis of syphilis (TPHA) - LAZAR, Voichitza; KEVORKIAN, Florica; CĂPUŞAN, Iuliu; AUSLANDER, Dezideriu; VERESS, Eva (Archives of Acoustics, 1984)
The preparation of the antigen for TPHA sonicated suspension of T. pallidum (Nichols strain) being so far a "secret" of the procedures, we have attempted to reproduce it by our own means of ultrasonic irradiation. The best results in agreement with the standard reactions for syphilis were obtained by sonicating T. pallidum suspensions for a duration of 20 min. by the following parameters of the ultrasonic field: frequency 1 MHz, intensity 0.9 W/cm^2. Using this method we obtained microfragments of 1-1.3 microns. The most reliable dilution for the antigen was 1/1000. The haernagglutination was performed in 30 patients with different forms of late syphilis after treatment.The results were in agreement with the clinical diagnosis, being moresensitive and consistent compared with the classical and standard reactions.